Dielectric behavior of lanthanum added barium strontium titanate borosilicate glass ceramics - Yadav A.K.; Gautam C.R.; Singh P. (My University, 2025)
Barium strontium titanate borosilicate glasses were prepared by melt-quench method and subsequent crystallization by regulated heat treatment process. The dielectric behavior of investigated glass ceramic samples shows a diffuse phase transition. The double relaxation was observed in one of the glass ceramic samples due to crystallographic transition from orthorhombic to tetragonal and tetragonal to cubic structure with change in temperature. The peak values of dielectric constant and dielectric loss of this glass ceramic sample was found to be 48,289 and 0.01, respectively, at frequency 20 Hz. Lanthanum oxide served the purpose of nucleating agent for crystallization of glass ceramics and hence, enhances the value of dielectric constant. Such glass ceramics may be used in making capacitors for high energy storage purpose. © 2015, Springer Science+Business Media New York.